Study the Effect of COVID-19 Disease on Thyroid Hormones (T3, T4, TSH) and the Lipid Profile in Recovering Iraqi Subjects - Salman, Zainab Zouher; Mohammed, Sanad Baqer; Muhi, Samer Abdulhasan (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2024)
The present pandemic of Coronavirus Disease 2019 (COVID-19) causes a multitude of lasting impacts on the human body. It has immediate and extensive effects on the human body, particularly the thyroid gland. A rise in adenylyl cyclase 2 (ACE2) and transmembrane serine protease 2 (TMPRESS2) makes it easier for viruses to get into human cells. COVID-19 triggers a hyperactive immune response that produces interleukin-6 (IL-6) and other pro-inflammatory cytokines. This hyperactive immune response leads to severe thyroid malfunction. The current study aimed to research the relationship between the recovering Iraqi subjects of COVID-19 and thyroid hormones and lipid profiles. This study aims to evaluate triiodothyronine (T3), thyroxine (T4), thyroid stimulating hormone (TSH), and lipid profile including cholesterol, high-density lipoprotein (HDL), triglycerides (TG), low-density lipoprotein (LDL), and very low-density lipoprotein (VLDL). A total of 70 recovering subjects with COVID-19 were collected, and 50 were used as a control group. Thyroid hormones showed significant differences, an increase in serum TSH, and a decrease in the levels of T3 and T4 between the two groups (p= 0.001). The lipid profile revealed notable variations, as well as an increase in cholesterol, LDL, and VLDL. There was a notable drop in HDL levels between the two groups, as indicated through p-values of 0.001. Body mass index (BMI) and age did not show any significant differences. This research concludes that recovered people from COVID-19 had problems with their thyroid hormones and lipid profiles.